Operations research modeling of the taxi transport between Polokwane and Mankweng in the Limpopo Province, South Africa. - Nkoane, Simon Setsweke (My University, 2009)
This study is focused on the scheduling of minibus (taxi) transport between the City of Polokwane and Mankweng Township in the Limpopo Province of South Africa. New formulations of integer programming for taxi timetabling problems were presented. The problem is modeled as a single link transit. Hard and soft constraints have been identified. The main objective of the study is to design the best schedule that minimizes the waiting time of passengers and provides better service to the public for taxi transport on the aforementioned link. In this study the proposed solution methods managed to produce a timetable with a non-conflicting set of taxis and no consecutive assignment of one taxi to the trips within a duration time (total time traveled on a return trip between two locations). Local search algorithms such as the Genetic Algorithm are used in the research, mainly due to its flexibility and power to produce the best solution to the timetabling problems. The algorithm starts with a population of a feasible search space. Two operators: mutations and crossovers, were designed in such a way that they do not produce infeasible offspring.
Thesis (M.Sc.) (Operations Research) --University of Limpopo, 2009.
Keywords: Taxi transport